Survey highlights important discrepancies between definitions of paediatric abnormal growth taught to medical students in 23 European countries. (5th March 2018) - Scherdel, Pauline; Hjelm, Nils; Salaün, Jean‐François; ,; Heude, Barbara; Chalumeau, Martin
Abstract: Aim: This study compared the definitions of abnormal growth that are taught across Europe to explain previously reported variations in growth‐monitoring practices. Methods: We developed two online surveys in 2016 to obtain the definitions of abnormal growth in European countries and approached the national chairs of the European Confederation of Primary Care Paediatricians in 18 countries and the International Federation of Medical Students' Associations in 33 countries. Results: We obtained definitions from 10 of 18 paediatricians and 18 of 33 students, covering 23 of the 33 European countries surveyed. Abnormal faltering growth was always defined, either by a single parameter (24%) or combined parameters (76%). Four static parameters were used: standardised height (100%), standardised weight (60%), standardised body mass index (12%) and distance to target height (20%). Two dynamic parameters were used: growth deflection (28%) and growth velocity (32%). The thresholds used to define abnormal faltering growth varied slightly in some cases and widely in others. Abnormal accelerated growth appeared in 52% of the definitions, with important variations in parameters and thresholds. Conclusion: There were important between‐country discrepancies in the definitions of paediatric abnormal growth that were taught in 23 European countries. Standardisation is vital. Abstract :